Driving Economic Competitiveness through Innovation and Differentiation Strategies - Lailaturrahmah MD , Khoirunnisa; Danial, R Deni Muhammad; Zafar, Tetty Sufianty (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of innovation capability on competitive advantage, with differentiation strategy as a mediating variable, among Micro, Small, and Medium Enterprises (MSMEs) engaged in the early morning snack market at Toserba Selamat, Sukabumi City. Employing a quantitative research design, data were collected from 270 MSME respondents using a structured questionnaire. The analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The findings reveal that innovation capability has a significant positive effect on both differentiation strategy and competitive advantage. Additionally, differentiation strategy plays a mediating role in strengthening the impact of innovation capability on competitive advantage. These results highlight the importance of fostering innovation among MSMEs, not only as a means of adapting to dynamic market conditions but also as a strategic foundation for creating distinctive offerings that enhance market competitiveness. The study provides practical implications for MSME development through innovation-driven differentiation strategies.